Prediction of medication non‐adherence and associated outcomes in pediatric kidney transplant recipients. (28th April 2015) - Connelly, James; Pilch, N.; Oliver, M.; Jordan, C.; Fleming, J.; Meadows, H.; Baliga, P.; Nadig, S.; Twombley, K.; Shatat, I.; Taber, D.
Abstract Studies have continued to evaluate risk factors associated with post‐transplant non‐adherence in pediatric patients. However, many of these studies fail to evaluate how risk factors can be utilized to predict MNA. The aims of this study were to (i) determine salient risk factors associated with MNA to develop an adequate predictive risk model and (ii) assess transplant outcomes based on the presence of MNA in a large, diverse cohort of pediatric KTX recipients. One hundred and seventy‐five solitary pediatric KTX recipients transplanted from 1999 to 2013 were included. AA, males, older patients, those who lived in urban environments, had legal issues, and lived shorter distances from the transplant center were more likely to have MNA. Using logistic regression, a parsimonious model applying nine risk factors together was developed for predicting MNA, demonstrating a PPV of 69% and a NPV of 81%. Patients with MNA had more than twice the risk of biopsy proven acute rejection, 1.6 times the risk of hospitalization, and 1.8 times the risk of graft loss. Utilization of a predictive model to determine risk of MNA after pediatric KTX may offer clinicians the ability to efficiently and effectively monitor MNA following transplant.